Relative Effects of Age, Race, and Stage on Mortality in Gestational Choriocarcinoma. Issue 2 (1st February 2018) - Tarney, Christopher M.; Tian, Chunqiao; Craig, Eric R.; Crothers, Barbara A.; Chan, John K.; Gist, Glenn D.; Bateman, Nicholas W.; Conrads, Thomas P.; Hamilton, Chad A.; Larry Maxwell, George; Darcy, Kathleen M.
Abstract : Objective: Gestational choriocarcinoma is a malignant form of gestational trophoblastic disease that usually arises after a molar pregnancy, but may follow any antecedent pregnancy. Investigations in this rare cancer are limited. We evaluated the prognostic effects of age, race, and stage in choriocarcinomas diagnosed for 4 decades. Methods: Patients diagnosed as having gestational choriocarcinoma between 1973 and 2014 from the Surveillance, Epidemiology, and End Results program were eligible. Relationships with overall survival and cancer-specific survival were evaluated using log-rank testing and Cox modeling. Multivariate analyses included adjustments for age, race, and stage. Results: There were 947 patients with choriocarcinoma including 403 non-Hispanic white (NHW) patients, 473 with distant stage, and 142 who died. Median age at diagnosis was 25 years for non-Hispanic black (NHB) patients and 35 years for Asian/Pacific Islanders (API) compared with 29 years for NHW patients ( P = 0.0001). Five-year overall survival varied between 82% and 92% when diagnosed at the age of at least 40 years compared with less than 20 years ( P < 0.0001), and from 85% to 95% in patients with distant vs local disease ( P < 0.0001), respectively. Multivariate analysis demonstrated that age, race, and stage were independent predictors of mortality. Risk of death increased incrementally in patients diagnosed at 20 to 39 years of age (adjusted hazard ratio [aHR], 3.87; 95% confidence interval [CI], 1.69–8.86; P = 0.001) and at least 40 years of age (aHR, 7.18; 95% CI, 2.95–17.49; P < 0.0001) compared with 20 years or younger. Non-Hispanic black patients were the only racial group at higher risk of death compared with NHW patients (aHR, 1.86; 95% CI, 1.22–2.82; P < 0.004). Distant vs local disease added an additional risk of death (aHR, 2.43; 95% CI, 1.57–3.75; P < 0.0001) over that attributable to age at diagnosis and NHB race. Similar relationships to cancer-specific survival were also observed ( P < 0.05). Conclusions: Most patients with choriocarcinoma have excellent prognosis. However, NHB patients and patients who are diagnosed at the age of at least 20 years or have distant stage have significantly worse mortality.